Semantic Operation of Place in the Legendary Movie: حيدر وسم صالح (Al-Academy, 2021)
Place is considered one of the important artistic elements in the movie through which the events occur in different arts and literatures and with its absence there isn’t any that can initiate events. Place is important for the things that we recognize, and the first fact in cinema is the place which can't be dispensed with on the level of the film or scene or cinematic shot that can't be emptied from its spatial content. The characters are always there in a place occupying some space of it, despite that it is not merely a container for the event cinematically. The researcher views the importance of discovering and observing them in this research which is divided into four chapters as follows: (theoretical framework) which includes the research problem which is crystallized in the following cognitive question: (what are the semantic operations of place in the legendary movie?) Then the research objective in discovering the semantic operation of place in the legendary movie. It is temporally determined by (2010) and spatially by the legendary movie in the American cinema, in addition to the procedural definitions for the research terms. As for (the theoretical framework), it has been divided into two sections. The first is titled (place indications in the cinema movie), and the second titled (legend and cinema), reaching to the most important indications of the theoretical framework. As for (the research procedures) which addressed (the research methodology, community, tool, analysis unit and the sample in addition to the results and conclusions), it has been dedicated to discuss the results of the study sample and reach at the most important conclusions. The research ended the research with the list of sources